THE RATES OF MORTALITY FROM CIRCULATORY DISEASES IN THE WORKING-AGE POPULATION OF UKRAINE - Ivanyuk, A.V.; Orlova, N.M.; Kaniura, O.A. (World of Medicine and Biology, 2021)
The authors of the paper aimed to determine the general trends and regional features of mortality of the working age population from diseases of the circulatory system in Ukraine in 2015-2019. It was found that in 2019, circulatory diseases caused every third (33.4 %) case of death of the working-age population in Ukraine. The probability of death from this pathology at working age in Ukraine is 2 times higher than the European mean and 4.6 times higher than in the European Union. The mortality rate of the rural population from diseases of the circulatory system is 19.5 % higher than in the urban population. Losses of the working-age population have a stable territorial profile and negative dynamics in most regions of Ukraine, which necessitates the adoption of targeted regional programs aimed at improving the prevention of circulatory diseases and the organization of cardiac and cardiological surgery.
Keywords: circulatory diseases; mortality; working age population